REPRESENTATION OF LANGUAGE AND CULTURE IN EDUCATION - Wardiah, Dessy (Jurnal Dosen Universitas PGRI Palembang)
This paper aims to provide a description representations theaspects of language and culture in education by examiningseveral theories and expert opinions. The method used in this paper is a qualitative descriptive method, which means to understand a phenomenon in the social context naturally with the advanced process of interaction between researchers indepth communication with the phenomenon to be studied through the surgical literature. From the discussion, it can be synthesized that language is a vehicle and a cultural product. Language reflects the culture of the doers or users. Because it is a language in addition to functioning as a means of communication, language is also an implementation of culture in education Cultural formed values and norms indirectly in form of language that be realized in the educational process. When it is related with education in Indonesia, the language has a central role in the development of intellectual, social, and emotional learners and it works as supporting of success in studying a field of science.Keywords: Language, Culture, andEducation